2016
DOI: 10.1002/ajp.22610
|View full text |Cite
|
Sign up to set email alerts
|

Leaf swallowing and parasite expulsion in Khao Yai white‐handed gibbons (Hylobates lar), the first report in an Asian ape species

Abstract: Leaf swallowing behavior, known as a form of self-medication for the control of nematode and tapeworm infection, occurs widely in all the African great apes (Pan troglodytes schweinfurthii, P. t. troglodytes, P. t. verus, P. t. vellerosus, Pan paniscus, Gorilla gorilla graueri), except mountain gorillas. It is also reported to occur in a similar context across a wide array of other animal taxa including, domestic dogs, wolves, brown bears, and civets. Despite long-term research on Asian great and small apes, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Additional unknown factors may be involved, warranting further investigation. An understanding of the reasons behind the unusually high frequency of leaf swallowing at this site, may lead to a broader understanding of the behaviour in great apes and indeed other species that also exhibit this behaviour [ 99 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional unknown factors may be involved, warranting further investigation. An understanding of the reasons behind the unusually high frequency of leaf swallowing at this site, may lead to a broader understanding of the behaviour in great apes and indeed other species that also exhibit this behaviour [ 99 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chimpanzees, for example, chew the piths of Vernonia amygdalina and swallow Aspilia leaves, which are thought to facilitate the expulsion of intestinal nematodes and cestodes (Huffman, 2001). Gibbons in Thailand are also thought to use Gironniera nervosa leaves for similar purposes (Barelli and Huffman, 2017). A recent comparative analysis found that primate species with a larger absolute brain are more likely to self-medicate, suggesting that self-medication is, to some degree, cognitively demanding (Neco et al, 2019).…”
Section: Mechanism 12: Cognitive Abilities Help To Avoid or Respond mentioning
confidence: 99%
“…Moreover, alive and motile parasites or parasite fragments have been found trapped or attached to the leaves' surface in the dung after some hours of leaf‐swallowing (e.g., nematode Oesophagostomum stephanostomum , Huffman et al, 1996; tapeworm Bertiella studeri , Wrangham, 1995). Recently, leaf‐swallowing and parasite expulsion ( Streptopharagus pigmentatus ) was reported for the first time in an Asian ape species, the gibbon ( Hylobates lar , Barelli & Huffman, 2016). This suggests that this adaptive self‐medicative behavior is not restricted to African great apes and might occur more widely than previously found.…”
Section: Discussionmentioning
confidence: 99%
“…More often than not, direct or indirect observations of self‐medication in primates are not the specific focus of research, but unexpected events during field data collection (Huashuayo‐Llamocca & Heymann, 2017; Morrogh‐Bernard et al, 2017; Wrangham, 1995; Wrangham & Nishida, 1993). Therefore, more focused efforts and research on long‐term study sites with well‐habituated primate groups are important sites for future systematic investigations of self‐medication (e.g., Barelli & Huffman, 2016). Furthermore, besides a systematic and intensive sample collection, researchers from different research areas, such as ethnobotany, behavioral ecology, primatology, and pharmacology, should collaborate and integrate their field and laboratory research in future multidisciplinary studies to further advance this topic.…”
Section: Discussionmentioning
confidence: 99%